A review of codebook design methods for sparse code multiple access - Syed Aamer Hussain; Norulhusna Ahmad; Ibraheem Shayea; Hazilah Mad Kaidi; Liza Abdul Latiff; Norliza Mohamed; Suriani Mohd Sam (Institute of Advanced Engineering and Science, 2021)
The progressions in telecommunication beyond the 5th generation have created a need to improve research drifts. The current 5G study has an important focus on non-orthogonal multiple access (NOMA) technology. sparse code multiple access (SCMA) is a promising technique within NOMA, enhancing the multi-user handling capability of next-generation communication. In the SCMA sphere, codebook designing and optimisation are essential research matters. This study conversed with different codebook design practises existing in the literature, analysing them for numerous parameters, including bit error rate (BER), an optimisation technique, and channel settings. From the analysis, the paper presents the efficiency of different approaches. The article also discusses the prospects and challenges of SCMA optimisation in practical implementation in various domains.